EFFECTIVENESS OF E-POSYANDU HEALTH (EPOK) APPLICATION ON KNOWLEDGE AND SKILLS OF POSYANDU CADRES IN MONITORING GROWTH AND DEVELOPMENT OF TODDLERS - Damayanti, Melly; Nurul Aini Suria Saputri; Vina Jayanti; Ika Susanti (Bajang Institute, 2024)
Posyandu cadres are community elements that play an important role in the implementation of Posyandu activities. The cadre’s role includes monitoring the growth and development of children under the age of five. To do their job effectively, they must have strong monitoring knowledge and skills in order to detect complications or problems in toddlers early on. So that appropriate intervention and counseling can begin immediately. The ePoK application is an innovative smartphone application that helps cadres monitor the growth and development of toddlers. The objective of this study was to determine the effectiveness of the ePoK application in terms of posyandu cadres’ knowledge and skills in monitoring toddler growth and development. This study was a quasi-experiment with a one-group pretest and posttest design. This study was carried out in Tanjungpinang City. A total of 60 posyandu cadres responded. Respondents were given the ePoK Application to use for one month. Knowledge was assessed using a questionnaire, and skills were assessed using a checklist. The results showed that respondents’ knowledge and skills increased both before and after using the application (11.55 and 5.78, respectively). There was also a significant difference in the knowledge and monitoring skills of respondents before and after using the ePoK Application with a p value <0.05 (0.000<0.05). The conclusion of this study is that the use of the ePoK application is proven to increase the knowledge and skills of posyandu cadres on monitoring the growth and development of toddlers.